Androgen deprivation-induced elevated nuclear SIRT1 promotes prostate tumor cell survival by reactivation of AR signaling. (1st May 2021) - Huang, Shih-Bo; Thapa, D.; Munoz, A.R.; Hussain, S.S.; Yang, X.; Bedolla, R.G.; Osmulski, P.; Gaczynska, M.E.; Lai, Z.; Chiu, Yu-Chiao; Wang, Li-Ju; Chen, Y.; et al.
Abstract: The NAD + -dependent deacetylase, Sirtuin 1 (SIRT1) is involved in prostate cancer pathogenesis. However, the actual contribution is unclear as some reports propose a protective role while others suggest it is harmful. We provide evidence for a contextual role for SIRT1 in prostate cancer. Our data show that (i) mice orthotopically implanted with SIRT1 -silenced LNCaP cells produced smaller tumors; (ii) SIRT1 suppression mimicked AR inhibitory effects in hormone responsive LNCaP cells; and (iii) caused significant reduction in gene signatures associated with E2F and MYC targets in AR-null PC-3 and E2F and mTORC1 signaling in castrate-resistant ARv7 positive 22Rv1 cells. Our findings further show increased nuclear SIRT1 (nSIRT1) protein under androgen-depleted relative to androgen-replete conditions in prostate cancer cell lines. Silencing SIRT1 resulted in decreased recruitment of AR to PSA enhancer selectively under androgen-deprivation conditions. Prostate cancer outcome data show that patients with higher levels of nSIRT1 progress to advanced disease relative to patients with low nSIRT1 levels. Collectively, we demonstrate that lowering SIRT1 levels potentially provides new avenues to effectively prevent prostate cancer recurrence. Highlights: High nuclear SIRT1 (nSIRT1) levels was associated with a significantly increased risk of prostate cancer progression. Androgen deplete conditions increased nuclear accumulation of SIRT1 protein. SIRT1 suppression impacts distinct pathways as a function of the state of the disease. SIRT1 inhibition in essence may have utility in prevention of primary prostate cancer outcomes. Combination of SIRT1 inhibitors with AR targeted therapy may be useful in advanced metastatic disease.